LNCRNA LY86-AS1 EXPRESSION ON T2DM AGED 40 YEARS OVER IN MUNGGU SOCIETY - Laksmita, W Ayu Saka; Widayanti, Ni Putu; Apriyanthi, Desak Putu Risky Vidika; Arijana, I G K Nyoman (LIFE: International Journal of Health and Life-Sciences, 2020)
Diabetes mellitus type 2 (T2DM) is the most common health problem found in almost all over the world. T2DM sufferers need long-term care and treatment to prolong life and improve their life quality. Long noncoding RNA (lncRNA) is a part of noncoding RNA that was recently created with various human diseases. This research aims to explore the analysis of lncRNA LY86-AS1 as a diagnostic marker for T2DM. This study is quantitative descriptive using simple random sampling technique. Blood samples were taken from 10 respondents of Munggu society. Extracted RNA was used to synthesize complementary DNA with Reverse Transcription Kit. Quantitative real-time PCR has doneby SYBR Green. PCR analysis was performed with quantitative analysis by conducting 10 samples. The result found was the decrease in lncRNA LY86-AS1 expression. From this it can be concluded the possibility of using lncRNA LY86-AS1 for detecting diagnostic markers of T2DM sufferers for Munggu society.